2016
DOI: 10.1002/ar.23351
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic Development of the Derived Olfactory System of the Mantellid Frog Mantidactylus betsileanus

Abstract: The nasal cavity of Mantidactylus betsileanus, a frog of the Madagascar-Comoroan endemic family Mantellidae, is characterized by a unique internal architecture. Unlike the state commonly observed in anurans, the two discernible olfactory subsystems of M. betsileanus (the main olfactory organ and the vomeronasal organ) are anatomically separated from each other, suggesting an enhanced functional differentiation. Here we evaluate the ontogenetic formation of this extraordinary anatomical state based on a histolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…The controlled transport of selected stimuli into the sequestered VNO might be facilitated by specific binding proteins in secretions from the harderian gland or the lateral nasal gland (LNG). The LNG opens directly above the (obstructed) conduit between MOO and VNO in mantellines, at the lateral wall of the nasal cavity (Nowack & Vences, ), similar to the state in frogs with generalized nasal anatomy (Nowack, ). The opening of the nasolacrimal duct into the CM (Fig.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The controlled transport of selected stimuli into the sequestered VNO might be facilitated by specific binding proteins in secretions from the harderian gland or the lateral nasal gland (LNG). The LNG opens directly above the (obstructed) conduit between MOO and VNO in mantellines, at the lateral wall of the nasal cavity (Nowack & Vences, ), similar to the state in frogs with generalized nasal anatomy (Nowack, ). The opening of the nasolacrimal duct into the CM (Fig.…”
Section: Discussionmentioning
confidence: 94%
“…We studied the anatomy of the olfactory organ of five mantellid species, and compared it with the derived state found in Mantidactylus (Junk et al, 2014;Nowack & Vences, 2016) and with the generalized state found in Rhacophorus (Watanabe, 1936;Junk et al, 2014), a representative of the sister taxon of mantellids.…”
Section: Comparative Anatomy Of the Olfactory Organ In Mantellidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The morphology of the olfactory system in adult stages has been studied in great detail in ranids (Døving, Trotier, Rosin, & Holley, 1993;Gaupp, 1904;McCotter, 1917;Tsui, 1946), in basal anurans (Benzekri & Reiss, 2012;Stephenson, 1951;Wagner, 1934), and in pipids (Dit- surveys across anurans (Helling, 1938;Jurgens, 1971). These studies have shown that the general morphology and organization of this system are shared by the majority of anurans, with the exception of the pipids and ascaphids, in which certain morphological peculiarities have been described as related to the aquatic habits of adults (Paterson, 1951;Reiss & Eisthen, 2008), and in the recently described deviant anatomy of the mantellid Mantidactylus betsileanus (Junk et al, 2014;Nowack & Vences, 2016), where the functional significance appears to relate to perception of femoral gland pheromone secretions (Nowack et al, 2017). The analysis of the adult morphology of the nose in ceratophryid frogs also reveals a somewhat deviant morphology in adult stages of the aquatic Lepidobatrachus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Increased size of the head in females may indicate an increased cranial volume and vomeronasal organ. This would be a logical evolutionary outcome in view of the transmission of volatile compounds from the males' femoral glands to the females' vomeronasal organ during courtship (Nowack & Vences, 2016;Nowack et al, 2017). Larger sterna and phalanges may likewise aid the female biomechanically in maintaining her vertical position during the reproductive act (Altig, 2008) by increasing muscle attachment area and potentially providing longer input levers relative to output levers.…”
Section: Intraspecific Osteological Variation In Blommersia Transmarinamentioning
confidence: 99%